Case report: Checkpoint inhibitor pneumonitis with positive anti-melanoma differentiation-associated gene 5 antibodies in a patient with lung cancer - Pan, Siqi; Xie, Huaiya; Wang, Luo; Wang, Yuanzhuo; Zou, Menglian; Xu, Yan; Tian, Xinlun; Fan, Junping; Wang, Jinglan (Frontiers in Immunology, 2024)
With the widespread use of immune checkpoint inhibitors to treat various cancers, pulmonary toxicity has become a topic of increasing concern. Anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibodies are strongly associated with rapidly progressive interstitial lung disease (RP-ILD) in patients with clinically amyopathic dermatomyositis. However, anti-MDA5 antibody expression has not been reported in patients with immune-related adverse events. We present the case of a 74-year-old man with lung adenocarcinoma who developed RP-ILD after treatment with immune checkpoint inhibitors. Further investigation revealed multiple autoantibodies, including anti-MDA5 antibodies. He initially responded to systemic glucocorticoids, immunosuppressants, and tocilizumab but eventually died from worsening pneumomediastinum. This case is the first one to suggest that checkpoint inhibitor pneumonitis can present as RP-ILD with positive anti-MDA5 antibodies, which may be predictive of a poor prognosis.